2012
DOI: 10.1152/jn.00619.2011
|View full text |Cite
|
Sign up to set email alerts
|

Closely overlapping responses to tools and hands in left lateral occipitotemporal cortex

Abstract: Bracci S, Cavina-Pratesi C, Ietswaart M, Caramazza A, Peelen MV. Closely overlapping responses to tools and hands in left lateral occipitotemporal cortex. J Neurophysiol 107: 1443-1456, 2012. First published November 30, 2011 doi:10.1152/jn.00619.2011.-The perception of object-directed actions performed by either hands or tools recruits regions in left fronto-parietal cortex. Here, using functional MRI (fMRI), we tested whether the common role of hands and tools in object manipulation is also reflected in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
154
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 171 publications
(175 citation statements)
references
References 61 publications
19
154
2
Order By: Relevance
“…More recently, Kanwisher and colleagues (Saygin et al, 2016; Osher et al, 2015) have presented compelling evidence that there is a high degree of topographical alignment between patterns of structural connectivity and patterns of category preferences. Another line of work by Peelen and colleagues (Bracci et al, 2012) has shown a tight coupling between neural specificity for hands and tools in lateral posterior temporal cortex and functional connectivity with somatosensory cortex. Taken together, we would suggest that a connectivity constrained account of the origin of category-specificity in the ventral stream is able to explain a set of facts that would otherwise seem disconnected on an account that prioritized visual experience as the principal source of organizational constraints that lead to biases by semantic domain:…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Kanwisher and colleagues (Saygin et al, 2016; Osher et al, 2015) have presented compelling evidence that there is a high degree of topographical alignment between patterns of structural connectivity and patterns of category preferences. Another line of work by Peelen and colleagues (Bracci et al, 2012) has shown a tight coupling between neural specificity for hands and tools in lateral posterior temporal cortex and functional connectivity with somatosensory cortex. Taken together, we would suggest that a connectivity constrained account of the origin of category-specificity in the ventral stream is able to explain a set of facts that would otherwise seem disconnected on an account that prioritized visual experience as the principal source of organizational constraints that lead to biases by semantic domain:…”
Section: Discussionmentioning
confidence: 99%
“…This denominator was chosen because the index would thus be less influenced by relative size differences between ROIs compared to other possibilities (e.g., the average size or the unique voxels in the two ROIs) (Bracci et al, 2012). The thresholds were set to p b 0.05 (Bonferroni corrected; fixed effect) for the scene localizer to separate PPA ROIs from those extending to elsewhere, and p b .01 (uncorrected, cluster size > 7 resampled voxels, 189 mm 3 ; random effect; resulting in a conjunction threshold of p b .001) for each contrast of the conjunction results of large nonmanipulable objects selectivity (large nonmanipulable > tool and large nonmanipulable > animal) in the sighted group's auditory, the blind group's auditory, and the sighted group's picture-viewing experiments.…”
Section: Relation Between Areas Showing Large Nonmanipulable Object Smentioning
confidence: 99%
“…The advent of fMRI has afforded us the opportunity to examine the brain mechanisms associated with tool use and it has revealed a number of left-hemisphere areas implicated in the use of vision for guiding actions (the dorsal stream from occipito-parietal cortex to motor cortex) and for recognizing objects (the ventral stream in occipito-temporal cortex; Goodale & Milner, 1992). Historically, to localize the "tool network", brain activity associated with viewing pictures of tools has been contrasted against activity when viewing pictures of control stimuli such animals, buildings (Chao & Martin, 2000), chairs (Bracci et al, 2012), scrambled images (Creem-Regehr & Lee, 2005), or other non-tool shapes. These contrasts have reliably identified tool-selective areas such as dorsal regions like the superior parietal lobule (SPL), ventral pre-motor cortex (PMv), and ventral areas like the middle temporal gyrus (MTG), particularly in the left hemisphere.…”
Section: Introductionmentioning
confidence: 99%